NPC Seven-Level Single-Phase Inverter with DC-Link Voltage Balancing, Input Voltage Boosting, and AC Power Decoupling - Robert Stala; Jakub Hachlowski; Adam Penczek (Energies, 2022)
This paper presents a novel concept of the DC-AC system with the input voltage boost ability, seven-level output voltage modulation, and the input AC current reduction at the double frequency of the output voltage. The system integrates the NPC full-bridge inverter which is composed of four-level legs and an active input voltage balancer (AIVB). The DC-link is composed of three capacitors connected in a series. The source of the energy is connected directly to the middle capacitor while the upper and lower capacitors of the DC-link are charged by the AIVB. The operation of the AIVB leads to balancing of the DC-link voltage and a three-fold boosting of the input voltage. The AIVB utilizes a novel switched-capacitor (SC) topology and can be designed as a low-volume quasi-magneticless converter with a simple open-loop control. One of the proposed methods of the control of the AIVB allows for a double frequency reduction in the input current. The application of the AIVB allows for the use of a seven-level NPC full-bridge (FB) inverter with a simple classic carrier-based PWM which is not applicable in the typical DC-link configurations. This paper presents the converter’s concept, its operation, control methods, and the results of simulations and experiments.